Differences in Type Characteristics of Peritoneal Membrane Using Peritoneal Equilibrium Test in End Stage Renal Disease Patients Undergoing Peritoneal Dialysis at Hasan Sadikin Hospital, Bandung - Budiman, Muhammad Fitriandi; Afiatin, Afiatin; Andhika, Rizky (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Background: Peritoneal dialysis (PD) clears solutes and removes fluids from the patient's body. PD failure is primarily due to the clearing of solutes and the removal of fluids. Due to overhydration, the high peritoneal equilibrium test (PET) group is at greater risk of technical failure and death than other groups. Objective: This study aimed to to determine the characteristics of PET in patients with end-stage renal failure undergoing peritoneal dialysis (PD) at Hasan Sadikin Hospital, Bandung. Methods: This study is a retrospective, descriptive, and cross-sectional investigation. Results: Of the 34 PD patients, the PET results were as follows: 47.1% for high average, 14.7% for high, 35.3% for low average, and 2.9% for low. There were no significant differences in most variables analyzed between the PET groups, including age, gender, etiology, comorbid diseases, history of hemodialysis (HD), residual renal function, and laboratory parameters such as hemoglobin, urea, creatinine, and albumin. The current blood glucose and body mass index (BMI) levels in the high PET group showed higher values and significant differences (p = 0.019 and p = 0.043, respectively). Conclusion: Blood glucose and BMI may be important factors that distinguish patients with high PET from other PET groups.